A framework for nurturing champions of digital innovation - Svea Horstmann; Katharina Drechsler; Leona Chandra Kruse (Information Systems and e-Business Management, 2025)
Information Systems (IS) champions enthusiastically promote a digital innovation project throughout its development by obtaining the necessary resources. These individuals shape the innovativeness of an organization, as they initiate digital innovation projects and lead them toward successful completion. We still know little about how these champions can be identified and nurtured in organizations. We follow the Design Science Research approach in developing a framework for nurturing IS champions that can guide human resource practitioners. Our framework offers a strategic view of the champion journey and prescribes recommendations for action. The design decisions were derived from literature on digital innovation and innovation champions, and the framework was subsequently refined and evaluated meticulously. The design underwent two stages based on expert interviews from the IT industry (formative evaluation) and was subsequently evaluated by experts in digital innovation project management and human resource development in the IT industry (summative evaluation). The results demonstrate the feasibility of the framework and offer further insights into the problem and solution space of nurturing IS champions.
Keywords: 650; IS champion; Digital innovation; Champion nurturing framework; Design science research